Comparison of Financial Performance Before and After the Implementation of PSAK 116 in Companies in the Transportation and Logistics Sector - Muhammad Mishbahul Munir; Grace Grace (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research analyzes the differences of the financial performance within transportation and logistics companies listed on the Indonesia Stock Exchange before and after the implementation of PSAK 116. Financial performance is measured using financial solvency ratios (DAR, DER, LTDtER), profitability ratio (ROA), and liquidity ratio (Current Ratio). The research used a comparative quantitative approach using panel data from 16 sample companies over an eight-year period (2016–2023), those were divided into the pre-implementation period (2016–2019) and the post- implementation period (2020–2023) of PSAK 116. The technique of data analysis used were include paired difference tests (Paired Sample t-Test and Wilcoxon Signed-Rank Test) after conducting the Shapiro–Wilk normality test. The hypothesis testing results indicate that the implementation of PSAK 116 has a statistically significant impact on DER, but does not have a significant effect on the other four financial performance ratios (DAR, LTDtER, ROA, and Current Ratio). Further qualitative analysis reveals those findings are caused by heterogeneous impacts, in the mean while the significance in DER is driven by the ratio’s sensitivity in companies with high leverage levels, furthermore the non-significance in other ratios is attributed to the materiality of lease transactions.